S1PR1 mediates Th17 cell migration from the thymus to the skin in health and disease - Engesser, Jonas; Wang, Huiying; Kapffer, Sonja; Kaffke, Anna; Peters, Anett; Paust, Hans-Joachim; Geissen, Markus; Krebs, Christian F.; Panzer, Ulf; Asada, Nariaki (Frontiers in Immunology, 2024)
Th17 cells play crucial roles in host defense and the pathogenesis of autoimmune diseases in the skin. While their differentiation mechanisms have been extensively studied, the origin of skin Th17 cells remains unclear. In this study, we analyzed single-cell RNA-sequencing data and identify the presence of Th17 cells in the human thymus. Thymic Th17 cells were characterized by high expression levels of Sphingosine-1-Phosphate Receptor 1 (S1PR1), a receptor crucial for T cell egress from lymphoid tissues. In mice, Th17 cell-specific knockout of S1pr1 resulted in the accumulation of Th17 cells in the thymus and a corresponding decrease in their numbers in the skin. Th17 cells that accumulated in the thymus exhibited a lower IL-17A production capacity compared to those in the skin, indicating that the local environment in the skin is important for maintaining the Th17 cell phenotype. Additionally, using a murine psoriasis model, we demonstrated that Th17 cell-specific knockout of S1pr1 reduced their migration to the inflamed skin, thereby ameliorating disease progression. Collectively, our data suggest that S1PR1 mediates Th17 cell migration from the thymus to the skin, thereby modulating their functional engagement in both homeostatic and inflammatory conditions.